Oral Rehabilitation with Removable Partial Denture of a Patient with Cleidocranial Dysplasia. (9th May 2020) - Ghomi, Ali Jamali; Soufdoost, Reza Sayyad; Barzegar, Mohammad Saeed; Hemmati, Mohammad Ali
Abstract : This case report describes the oral rehabilitation of a patient with cleidocranial dysplasia who received a removable partial denture along with silicone-based permanent soft liner to improve esthetic and masticatory function. This patient was the candidate of neither implant nor orthodontic treatment due to medical conditions, history of mandible fracture, age, and risk of fracture after mandibular teeth extractions. Cone-beam computed tomography has made it possible to obtain comprehensive information regarding the morphology and positional relationship of impacted supernumerary teeth. Also, proper collaboration between surgeon and prosthodontist helped to achieve significant improvements in patient's self-esteem, masticatory function, and esthetic.